OPTIMALISASI BIMBINGAN PERKAWINAN VIRTUAL DI KANTOR URUSAN AGAMA (KUA) PADA ERA DIGITAL (Studi Kasus di Kantor Urusan Agama (KUA) Kecamatan Jombang, Kabupaten Jombang) - Bandi Siswanto; Ahmad Faruq (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Ministry of Religion of the Republic of Indonesia, through the Directorate General of Islamic Community Guidance, Head of the Community Guidance Section Islam at the Ministry of Religion District, is implementing Law Number 1 Concerning Marriage of 1974, which states that the purpose of marriage is to create a happy and lasting family. Jombang in particular. The researcher then selected the research site at the District Religious Affairs Office in coordination with the Religious Affairs Office in each of the current sub-districts. District of Jombang. Jombang, who collaborate in virtual marital counseling Because of this, scholars are eager to learn more about it and formulate the problem as follows:: 1) What is the form of virtual marriage guidance at the District Religious Affairs Office? Jombang? Is it optimal to implement virtual marriage guidance at the District Religious Affairs Office? Jombang?, The nature of this research is descriptive research with field research with qualitative methods and empirical research approaches, and data sources both primary and secondary with data collection techniques consisting of observation, interviews and documentation.